Education About Anemia And Nutrition In Adolescent Girls - Pratiwi Puji Lestari; Bening Prawita Sari; Darmayanti Wulandatika (Comment: an International Journal of Community Development, 2020)
The increase in nutritional needs in adolescence is related to the acceleration of growth, where the nutrients that enter the body are used to increase body weight and height accompanied by an increase in the number and size of body cell tissues. in daily food consumption. Young women generally experience deficiencies of iron, calcium, and vitamin A. In addition, there are also deficiencies of vitamin B6, zinc, folic acid, iodine, vitamin D, and magnesium. One of the four nutritional problems being faced by developing countries, including Indonesia, is the problem of iron nutrition anemia. Teenage girls are among the vulnerable to suffer from anemia because young women are in their infancy and have menstruation every month which causes iron loss.The method of implementing this community service activity includes socialization to the Chairperson of the Foundation at the Puteri 'Aisyah Muhammadiyah Orphanage, Banjarmasin City for the implementation of community service activities regarding anemia prevention education in adolescents. Implementation of community service takes place according to the plan that has been made. The material was delivered and the discussion process took place during the education provision. Teens can understand the prevention of anemia in adolescents.